PENGARUH SIKAP, NORMA SUBJEKTIF, DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP INTENSI BERHENTI MEROKOK (StudiKasuspadaSiswaSMKN 2 Lamongan) - Suci Dwi Pratiwi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This studyaims to determinethe effect ofattitudes toward behaviour,subjectivenorm, andPerceivedBehavioralControl(PBC) on students SMKN 2 Lamongan. This studyusesquantitative methodsand the type of research is explanatory research. Samplingtechnique uses nonprobability sampling, and type of purposive sampling. Data were collected through a questionnaire with a scale model of semantic diferential variables measuring attitudes toward behaviour, subjective norms, and Perceived Behavioral Control (PBC) and in accordance with the intentions of the Theory of Planned Behavior (TPB) of Icek Ajzen. This study, the sample uses is 50 respondents aged 15-18 years on studentsSMKN 2 Lamongan. Analysis of data using multiple regression analysis. All data were analyzed using SPSS version 20 for Windows. The analysis showesthat the threefactorsof attitudes toward behaviour,subjectivenorm, andPerceivedBehavioralControl(PBC) has apositiveand significanteffectto the intentionto quit smoking. Hypothesis testing usingt testshowedthat thethreeindependentvariablesstudiedwas shown to significantlyaffectthe dependentvariablesintentionto quit smoking. Thenthroughthe F testcan be seen thatthe variableattitudes toward behaviour, subjectivenorm, andPerceivedBehavioralControl(PBC) have a significant effecttogetherinintentionto quit smoking. WhilevariablesPerceivedBehavioralControl(PBC) is a variablethathas themostdominantinfluencein theintentionto quit smoking. Keywords : attitudes toward behaviour, subjectivenorm, PerceivedBehavioralControl(PBC), and behavioral intention